To the development of graphics in central asia great scientists who have contributed - Botayev Ahmadali Ashurovich; Ergasheva Orifaxon Kholmurodovna; Ilyosjon Mamatov Ilhomovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This article deals with the development of the science of graphic and graphic geometry in the Central Asian region, the scientists who contributed to the science and their works related to the science of graphics, scientists, designers and architects directly engaged in geometric constructions and graphic images and used them to express their ideas. As a result, new graphic images have emerged, improved and evolved